If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 = 11 + -10b + 2b Combine like terms: -10b + 2b = -8b 11 = 11 + -8b Add '-11' to each side of the equation. 11 + -11 = 11 + -11 + -8b Combine like terms: 11 + -11 = 0 0 = 11 + -11 + -8b Combine like terms: 11 + -11 = 0 0 = 0 + -8b 0 = -8b Solving 0 = -8b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '8b' to each side of the equation. 0 + 8b = -8b + 8b Remove the zero: 8b = -8b + 8b Combine like terms: -8b + 8b = 0 8b = 0 Divide each side by '8'. b = 0 Simplifying b = 0
| s-3=-5 | | 210.00+0.15x=322.50 | | 4-2=10 | | 3x=2+-1y | | 10x+9=27+7x | | f(-1)=5x+5 | | -(a+3)=-2(2x+3)-7 | | 2(t+2)=14 | | 81xsquared+8=0 | | f=-1 | | 41(x-6)+4=6x-8 | | 9x+7(3x-4)=7-5x | | 4x-2(x-3)=-5+4x+1 | | 9v-9=3(v-5) | | 2x^2+x^2=25*25 | | 4-2(x-3)=5+4x+1 | | 4x-15=x+51 | | 0.5x+9= | | 208=-13 | | 12x^3+28x^2+13x-45=0 | | 3x+10=7x-5 | | 25x^4-50x^3+25x^2=0 | | 8y+2=4x | | 3x+20=41 | | X+(-3)+9=-1+14 | | h(t)=-4.9t^2+24t+8 | | 4x^7-32x^5= | | 34+20=41 | | 2x-38=180 | | x^2+24-11x= | | 27=7+4w | | e^10x+6=12 |